Computer-integrated electric-arc melting process control system - Дёмин, Дмитрий Александрович (Eastern-European Journal of Enterprise Technologies, 2014)
Developing common principles of completing melting process automation systems with hardware and creating on their basis rational choices of computer- integrated electricarc melting control systems is an actual task since it allows a comprehensive approach to the issue of modernizing melting sites of workshops. This approach allows to form the computer-integrated electric-arc furnace control system as part of a queuing system “electric-arc furnace - foundry conveyor” and consider, when taking automation decisions, not only the melting process itself, but also the associated processes such as casting, molding, equipment transportation. Several possible options for solving the problem of selecting means for software and hardware implementation of the melting control system at the melting-casting-molding workshop sites are presented. Such solutions include forming two- or three-level control systems, built according to the hierarchical principle. Implementing these recommendations, along with the optimal control algorithm for electric-arc melting in a furnace, considered as an element of the queuing system, allows to modernize the existing electric melting control systems